What is Translation History? A Trust-Based Approach - Rizzi, Andrea; Lang, Birgit; Pym, Anthony; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
"Without trust, the translation profession would collapse, and so would its practice. This innovative volume shows that trust is a wonderfully rich and revealing prism through which to study the history of both the practice and the profession." -- Andrea Chesterman, University of Helsinki, Finland "[This book] builds bridges between historians and translation scholars by theorizing translation in terms historians will understand and theorizing history in terms translation scholars will understand." -- Douglas Robinson, Hong Kong Baptist University This book presents a dynamic history of the ways in which translators are trusted and distrusted. Working from this premise, the authors develop an approach to translation that speaks to historians of literature, language, culture, society, science, translation and interpreting. By examining theories of trust from sociological, philosophical, and historical studies, and with reference to interdisciplinarity, the authors outline a methodology for approaching translation history and intercultural mediation from three discrete, concurrent perspectives on trust and translation: the interpersonal, the institutional and the regime-enacted. This book will be of particular interest to students and scholars of translation studies, as well as historians working on mediation and cultural transfer. Andrea Rizzi is a Cassamarca Associate Professor of Italian Studies and Australian Research Council Future Fellow at the University of Melbourne, Australia. Birgit Lang is Associate Professor of German Studies at the University of Melbourne, Australia. Anthony Pym is Professor of Translation Studies at the University of Melbourne, Australia, Distinguished Professor of Translation and Intercultural Studies at the Universitat Rovira i Virgili, Spain,and Professor Extraordinary at the University of Stellenbosch, South Africa.
Chapter 1: Introduction: Towards a New Translation History -- Chapter 2: On Relationality: Trusting Translators -- Chapter 3: On Relativity: Trusting Historians -- Chapter 4: On Interdisciplinarity: Trusting Translation History.
Keywords: Translating and interpreting; Comparative literature; Literature -- History and criticism; Social history; Culture -- Study and teaching; Language Translation; Comparative Literature; Literary History; Social History; Cultural Theory